Adhesion strength of brackets repeated bonding in the same surface of enamel and reconditioned with different techniques - Luque Luque, Hugo Javier (2008)
Bonding failures of brackets and the repositioning of them occur quite often during the orthodontic treatment. Upon this situation, the professional may choose to stick the same bracket or bond a new one. The purpose of this study was to evaluate changes of the bonding strength of reconditioned brackets with direct flame, microetching and new brackets attached several times on the same tooth surface in vitro. 60 healthy human premolars extracted for orthodontic reasons were randomly assigned to 3 groups: Group I reconditioned brackets with air abrasion; Group II: reconditioned brackets with flame; Group III: new brackets. All brackets were bonded with resin No Mix (Prime Dental Manufactuing INC). Initially, new brackets were bonded to all groups to determine initial bonding strength (first shear test), then were subjected to four tests using a universal testing machine. The results showed that bonding strength decreased in relation to the number of shear tests, however, reconditioned brackets with microetching showed significantly more adherence force than the new brackets and flames. Apparently, in the fourth share test maximum stress of occurred enamel so the retention of brackets base became irrelevant.